Ternary NiFeMn layered double hydroxides as highly-efficient oxygen evolution catalysts - Lu, Zhiyi; Qian, Li; Tian, Yang; Li, Yaping; Sun, Xiaoming; Duan, Xue (Chemical communications (Cambridge, England), 2016)
Layered double hydroxides (LDHs) are a family of layer materials that receive heightened attention. Herein a ternary NiFeMn-LDH is investigated with superior oxygen evolution activity, which is attributed to the Mn 4+ doping in the intralayer, which modifies the electronic structure and improves the conductivity of the electrocatalyst. A ternary NiFeMn-LDH with an optimized transition metal ratio is developed as an advanced catalyst for the oxygen evolution reaction.